Contexto de trabalho e saúde psíquica: caminhos e descaminhos da atuação dos professores-gestores em uma universidade pública federal - Melo, Angélica Andrade Ferreira de (2020)
The work has been various transformations and is influenced by the historical moment experienced. The work environment and the way people relate to it can contribute to the promotion or deterioration of psychic health. Considering the management of public universities is permeated by enormous challenges, the present study has as a general objective to apprehend how professors-managers perceive their work context and its influence on mental health. It is a qualitative research, of a descriptive type, which used the case study. Heads of Department were defined as participants. The data collect was carried out through two synchronous online focus groups, with six participants, totaling 12 managers. The data were analyzed using the content analysis. First, it was intended to understand how the experience of being a university manager has been. For that, it was necessary to know the way of arrival to management, understand that it involves a performance with different actuations (teaching, research, extension and management). In addition, this experience was portrayed through a positive and negative assessment of being in this professional performance. Then, aspects that facilitate and aspects that hinder of work were identified according to the participants' perception. The aspects most often cited as facilitators are the training offers, the help of computerized systems, and the collaboration received by the secretaries. The most cited restrictive elements are: difficulties in communicating with the units; barriers caused by computerized systems; absence of preparation and knowledge about management; the conflicting environment and the difficulty of reconciling interests; the process of purchasing and using financial resources; and excessive charging for productivity and overhead. When investigating the aspects perceived as potential generators of suffering, emotional distress and malaise, the following were cited: Interpersonal conflicts; Charging for productivity and overload; work simultaneously in research, teaching, extension and management; Difficulties in organizing time; Excess charges and short deadlines; Lack of legal support; Violence and disrespect; Lack of resources; and excessive bureaucracy. Finally, the participants presented some suggestions for improvements to their performance, highlighting the need for training and development of department heads and legal support to answer the processes that involve management. The study provided a diagnosis on the perception of Department Heads, as well as providing a diagnostic model through online focus groups. The suggestions presented may collaborate to improve actions related to university management.